Sectoral linkages and their influence on structural change: The case of China - Tao Jin; Zhihao Li (PLoS ONE, 2025)
Structural change is a fundamental aspect of a country's economic development process. Unlike traditional literature, our research integrates input-output analysis with a multisector general equilibrium model to investigate the role of sectoral input-output linkages throughout this process. By utilizing this framework and applying it to Chinese data, we find that sectoral input-output linkages are as critical as final demand in our analysis. The stability of the manufacturing sector and the prosperity of the services sector are significantly influenced by these linkages. Our findings remain robust in counterfactual analyses, even after modifying the model specifications. We apply methodologies from production networks research to elucidate the mechanisms by which linkages function. Through structural decomposition analysis, we identify the various components that constitute these driving forces. Ultimately, our results align closely with our baseline findings.